KNOWLEDGE MANAGEMENT FOR ENTREPRENEURIAL ECOSYSTEMS AND THE COGNITIVE GAPS PROBLEM - Porev, Sergey (Збірник наукових праць Черкаського державного технологічного університету. Серія: Економічні науки, 2018)
<p class="docData;DOCY;v5;9675;BAiAAgAABoQCAAADASQAAAUPJAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAB5IQAAAD4fAAABcwAAAAEGBgAAAAQFvUIPAAkGAAAAABoGVQAAAAEBAQQGHgAAAFQAaQBtAGUAcwAgAE4AZQB3ACAAUgBvAG0AYQBuAAUGHgAAAFQAaQBtAGUAcwAgAE4AZQB3ACAAUgBvAG0AYQBuABkGBAAAAGUAbgAbBgAAAAACwR4AAAUkAQAAAVUAAAABAQEEBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAFBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAZBgQAAABlAG4ACMUAAAAAwAAAAFQAaABlACAAYQByAHQAaQBjAGwAZQAgAGkAcwAgAGQAZQB2AG8AdABlAGQAIAB0AG8AIAB0AGgAZQAgAHAAcgBvAGIAbABlAG0AIABvAGYAIAB0AGgAZQAgAGsAbgBvAHcAbABlAGQAZwBlACAAbQBhAG4AYQBnAGUAbQBlAG4AdAAgAGkAbgAgAGUAbgB0AHIAZQBwAHIAZQBuAGUAdQByAGkAYQBsACAAZQBjAG8AcwB5AHMAdABlAG0AcwAgAAUSAQAAAVUAAAABAQEEBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAFBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAZBgQAAABlAG4ACLMAAAAArgAAAHcAaQB0AGgAIAB0AGgAZQAgAHAAYQByAHQAaQBjAGkAcABhAHQAaQBvAG4AIABvAGYAIAB1AG4AaQB2AGUAcgBzAGkAdABpAGUAcwAsACAAdwBoAGUAcgBlACAAawBuAG8AdwBsAGUAZABnAGUAIABlAHgAYwBoAGEAbgBnAGUAcwAgAHMAaABvAHUAbABkACAAYgBlACAAaQBuAHQAZQBuAHMAaQB2AGUALgAgAAVqAAAAAVUAAAABAQEEBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAFBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAZBgQAAABlAG4ACAsAAAAABgAAAEkAdAAgAAVqAAAAAVUAAAABAQEEBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAFBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAZBgQAAABlAG4ACAsAAAAABgAAAHcAYQBzAAV6AAAAAVUAAAABAQEEBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAFBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAZBgQAAABlAG4ACBsAAAAAFgAAACAAaQBtAHAAbwByAHQAYQBuAHQAIAAFgAAAAAFVAAAAAQEBBAYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4ABQYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4AGQYEAAAAZQBuAAghAAAAABwAAABmAG8AcgAgAG8AdQByACAAcwB0AHUAZAB5ACAABXoAAAABVQAAAAEBAQQGHgAAAFQAaQBtAGUAcwAgAE4AZQB3ACAAUgBvAG0AYQBuAAUGHgAAAFQAaQBtAGUAcwAgAE4AZQB3ACAAUgBvAG0AYQBuABkGBAAAAGUAbgAIGwAAAAAWAAAAdABvACAAZABlAGYAaQBuAGUALAAgAAVoAAAAAVUAAAABAQEEBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAFBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAZBgQAAABlAG4ACAkAAAAABAAAAGkAcwAF0gAAAAFVAAAAAQEBBAYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4ABQYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4AGQYEAAAAZQBuAAhzAAAAAG4AAAAgAHQAaABlACAAbgBvAHQAaQBvAG4AIABvAGYAIABhACAAYwBvAG0AbQBvAGQAaQB0AHkAIABjAG8AdQBsAGQAIABiAGUAIAB1AHMAZQBkACAAdABvACAAawBuAG8AdwBsAGUAZABnAGUALgAgAAWGAAAAAVUAAAABAQEEBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAFBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAZBgQAAABlAG4ACCcAAAAAIgAAAEkAdAAgAGkAcwAgAHMAaABvAHcAbgAgAHQAaABhAHQAIAAFZgAAAAFVAAAAAQEBBAYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4ABQYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4AGQYEAAAAZQBuAAgHAAAAAAIAAAB0AAVoAAAAAVUAAAABAQEEBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAFBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAZBgQAAABlAG4ACAkAAAAABAAAAGgAZQAFZgAAAAFVAAAAAQEBBAYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4ABQYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4AGQYEAAAAZQBuAAgHAAAAAAIAAAAgAAVsAAAAAVUAAAABAQEEBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAFBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAZBgQAAABlAG4ACA0AAAAACAAAAHUAcwBlACAABWoAAAABVQAAAAEBAQQGHgAAAFQAaQBtAGUAcwAgAE4AZQB3ACAAUgBvAG0AYQBuAAUGHgAAAFQAaQBtAGUAcwAgAE4AZQB3ACAAUgBvAG0AYQBuABkGBAAAAGUAbgAICwAAAAAGAAAAbwBmACAABdAAAAABVQAAAAEBAQQGHgAAAFQAaQBtAGUAcwAgAE4AZQB3ACAAUgBvAG0AYQBuAAUGHgAAAFQAaQBtAGUAcwAgAE4AZQB3ACAAUgBvAG0AYQBuABkGBAAAAGUAbgAIcQAAAABsAAAAdABhAGMAaQB0ACAAYQBuAGQAIABlAHgAcABsAGkAYwBpAHQAIABrAG4AbwB3AGwAZQBkAGcAZQAgAGEAcwAgAG8AYgBqAGUAYwB0AHMAIABvAGYAIABtAGEAbgBhAGcAZQBtAGUAbgB0ACAABeAAAAABeQAAAAEBAQQGHgAAAFQAaQBtAGUAcwAgAE4AZQB3ACAAUgBvAG0AYQBuAAUGHgAAAFQAaQBtAGUAcwAgAE4AZQB3ACAAUgBvAG0AYQBuAAcGHgAAAFQAaQBtAGUAcwAgAE4AZQB3ACAAUgBvAG0AYQBuABkGBAAAAGUAbgAIXQAAAABYAAAAYwBvAG4AYwBlAGEAbABzACAAdABoAGUAIABjAG8AZwBuAGkAdABpAHYAZQAgAGcAYQBwAHMAIABiAGUAdAB3AGUAZQBuACAAcwB1AGIAagBlAGMAdABzAAWKAAAAAXkAAAABAQEEBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAFBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAHBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAZBgQAAABlAG4ACAcAAAAAAgAAACcABYoAAAABeQAAAAEBAQQGHgAAAFQAaQBtAGUAcwAgAE4AZQB3ACAAUgBvAG0AYQBuAAUGHgAAAFQAaQBtAGUAcwAgAE4AZQB3ACAAUgBvAG0AYQBuAAcGHgAAAFQAaQBtAGUAcwAgAE4AZQB3ACAAUgBvAG0AYQBuABkGBAAAAGUAbgAIBwAAAAACAAAAIAAFpAAAAAF5AAAAAQEBBAYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4ABQYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4ABwYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4AGQYEAAAAZQBuAAghAAAAABwAAABjAG8AbgBzAGMAaQBvAHUAcwBuAGUAcwBzACAABZwAAAABeQAAAAEBAQQGHgAAAFQAaQBtAGUAcwAgAE4AZQB3ACAAUgBvAG0AYQBuAAUGHgAAAFQAaQBtAGUAcwAgAE4AZQB3ACAAUgBvAG0AYQBuAAcGHgAAAFQAaQBtAGUAcwAgAE4AZQB3ACAAUgBvAG0AYQBuABkGBAAAAGUAbgAIGQAAAAAUAAAAYQBuAGQAIAB0AGUAeAB0AHMAIAAFkgAAAAF/AAAAAQEBBAYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4ABQYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4ABwYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4AGQYKAAAAZQBuAC0AVQBTAAgJAAAAAAQAAABvAHIABcAAAAABeQAAAAEBAQQGHgAAAFQAaQBtAGUAcwAgAE4AZQB3ACAAUgBvAG0AYQBuAAUGHgAAAFQAaQBtAGUAcwAgAE4AZQB3ACAAUgBvAG0AYQBuAAcGHgAAAFQAaQBtAGUAcwAgAE4AZQB3ACAAUgBvAG0AYQBuABkGBAAAAGUAbgAIPQAAAAA4AAAAIABvAHQAaABlAHIAIABtAGEAdABlAHIAaQBhAGwAIABwAHIAZQBzAGUAbgB0AGEAdABpAG8AbgAFigAAAAF5AAAAAQEBBAYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4ABQYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4ABwYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4AGQYEAAAAZQBuAAgHAAAAAAIAAABzAAWqAAAAAXkAAAABAQEEBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAFBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAHBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAZBgQAAABlAG4ACCcAAAAAIgAAACAAbwBmACAAaQBuAGYAbwByAG0AYQB0AGkAbwBuAC4AIAAFlAAAAAF5AAAAAQEBBAYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4ABQYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4ABwYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4AGQYEAAAAZQBuAAgRAAAAAAwAAABBAHUAdABoAG8AcgAFzAEAAAF5AAAAAQEBBAYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4ABQYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4ABwYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4AGQYEAAAAZQBuAAhJAQAAAEQBAAAgAHAAcgBvAHAAbwBzAGUAZAAgAHQAbwAgAHMAdQBwAHAAbABlAG0AZQBuAHQAIAB0AGgAZQAgAHMAdQBiAGoAZQBjAHQAaQB2AGUAIABjAG8AbQBwAG8AbgBlAG4AdAAgAG8AZgAgAGsAbgBvAHcAbABlAGQAZwBlACAAbQBhAG4AYQBnAGUAbQBlAG4AdAAgAHcAaQB0AGgAIAB0AGgAZQAgAG4AbwB0AGkAbwBuACAAbwBmACAAbwBwAGUAcgBhAHQAaQB2AGUAIABrAG4AbwB3AGwAZQBkAGcAZQAsACAAdwBoAGkAYwBoACAAYwBvAHIAcgBlAHMAcABvAG4AZABzACAAdABvACAAdABoAGUAIABjAG8AbgBjAGUAcAB0ACAAbwBmACAAawBuAG8AdwBsAGUAZABnAGUAIABhAHMAIAAFogAAAAF/AAAAAQEBBAYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4ABQYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4ABwYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4AGQYKAAAAZQBuAC0AVQBTAAgZAAAAABQAAABqAHUAcwB0AGkAZgBpAGUAZAAgAAWgAAAAAXkAAAABAQEEBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAFBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAHBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAZBgQAAABlAG4ACB0AAAAAGAAAAHQAcgB1AGUAIABiAGUAbABpAGUAZgAuAAWyAAAAAXkAAAABAQEEBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAFBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAHBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAZBgQAAABlAG4ACC8AAAAAKgAAACAATwBwAGUAcgBhAHQAaQB2AGUAIABrAG4AbwB3AGwAZQBkAGcAZQAgAAUWAQAAAXkAAAABAQEEBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAFBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAHBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAZBgQAAABlAG4ACJMAAAAAjgAAAG0AYQB5ACAAYgBlACAAZABlAGYAaQBuAGUAZAAgAGEAcwAgAGEAbABsACAAbwBmACAAdABoAGUAIAB3AG8AcgBkAHMAIABhAG4AZAAgAHAAaAByAGEAcwBlAHMAIABpAG4AIABjAG8AbgBzAGMAaQBvAHUAcwBuAGUAcwBzACwAIAB3AGgAaQBjAGgAIAAFuAAAAAF5AAAAAQEBBAYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4ABQYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4ABwYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4AGQYEAAAAZQBuAAg1AAAAADAAAABhAHAAcABlAGEAcgAgAHcAaABlAG4AIABhAHUAdABoAG8AcgAgAHMAZQBlAGsAIAAFjAAAAAF5AAAAAQEBBAYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4ABQYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4ABwYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4AGQYEAAAAZQBuAAgJAAAAAAQAAABhAG4ABYoAAAABeQAAAAEBAQQGHgAAAFQAaQBtAGUAcwAgAE4AZQB3ACAAUgBvAG0AYQBuAAUGHgAAAFQAaQBtAGUAcwAgAE4AZQB3ACAAUgBvAG0AYQBuAAcGHgAAAFQAaQBtAGUAcwAgAE4AZQB3ACAAUgBvAG0AYQBuABkGBAAAAGUAbgAIBwAAAAACAAAAIAAFGgEAAAF5AAAAAQEBBAYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4ABQYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4ABwYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4AGQYEAAAAZQBuAAiXAAAAAJIAAABvAHAAdABpAG0AYQBsACAAdgBlAHIAcwBpAG8AbgAgAHQAbwAgAHQAcgBhAG4AcwBtAGkAdAAgAG0AZQBuAHQAYQBsACAAawBuAG8AdwBsAGUAZABnAGUAIABpAG4AdABvACAAZQB4AHAAbABpAGMAaQB0ACAAbQBhAHQAZQByAGkAYQBsACAAZgBvAHIAbQAuAAU0AgAAAXkAAAABAQEEBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAFBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAHBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAZBgQAAABlAG4ACLEBAAAArAEAACAAQgB5ACAAdQBzAGkAbgBnACAAdABoAGUAIABjAG8AbgBjAGUAcAB0ACAAbwBmACAAbwBwAGUAcgBhAHQAaQB2AGUAIABrAG4AbwB3AGwAZQBkAGcAZQAsACAAYQB1AHQAaABvAHIAIABpAHMAIABkAGUAZgBpAG4AZQAgAHQAaABlACAAYwBvAGcAbgBpAHQAaQB2AGUAIABnAGEAcAAgAG8AZgAgAGEAYwB0AHUAYQBsAGkAegBhAHQAaQBvAG4AIABiAGUAdAB3AGUAZQBuACAAdABhAGMAaQB0ACAAYQBuAGQAIABvAHAAZQByAGEAdABpAG8AbgBhAGwAIABrAG4AbwB3AGwAZQBkAGcAZQAsACAAYQBuAGQAIABhAGwAcwBvACAAdABoAGUAIABjAG8AZwBuAGkAdABpAHYAZQAgAGcAYQBwACAAbwBmACAAZQB4AHQAZQByAG4AYQBsAGkAegBhAHQAaQBvAG4AIABiAGUAdAB3AGUAZQBuACAAbwBwAGUAcgBhAHQAaQBvAG4AYQBsACAAawBuAG8AdwBsAGUAZABnAGUABYAAAAABbwAAAAEBAQQGHgAAAFQAaQBtAGUAcwAgAE4AZQB3ACAAUgBvAG0AYQBuAAUGHgAAAFQAaQBtAGUAcwAgAE4AZQB3ACAAUgBvAG0AYQBuAAcGHgAAAFQAaQBtAGUAcwAgAE4AZQB3ACAAUgBvAG0AYQBuAAgHAAAAAAIAAAAgAAXYAAAAAX8AAAABAQEEBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAFBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAHBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAZBgoAAABlAG4ALQBVAFMACE8AAAAASgAAAGEAbgBkACAAdABoAGUAIABtAGEAdABlAHIAaQBhAGwAIABmAG8AcgBtACAAbwBmACAAaQBuAGYAbwByAG0AYQB0AGkAbwBuAC4ABeIAAAABfwAAAAEBAQQGHgAAAFQAaQBtAGUAcwAgAE4AZQB3ACAAUgBvAG0AYQBuAAUGHgAAAFQAaQBtAGUAcwAgAE4AZQB3ACAAUgBvAG0AYQBuAAcGHgAAAFQAaQBtAGUAcwAgAE4AZQB3ACAAUgBvAG0AYQBuABkGCgAAAGUAbgAtAFUAUwAIWQAAAABUAAAAIABJAHQAIABzAGgAbwB1AGwAZAAgAGIAZQAgAG4AbwB0AGUAZAAsACAAdABoAGEAdAAgAHQAaABlACAAYwBvAG4AYwBlAHAAdABzACAAbwBmACAABfQBAAABeQAAAAEBAQQGHgAAAFQAaQBtAGUAcwAgAE4AZQB3ACAAUgBvAG0AYQBuAAUGHgAAAFQAaQBtAGUAcwAgAE4AZQB3ACAAUgBvAG0AYQBuAAcGHgAAAFQAaQBtAGUAcwAgAE4AZQB3ACAAUgBvAG0AYQBuABkGBAAAAGUAbgAIcQEAAABsAQAAbwBwAGUAcgBhAHQAaQB2AGUAIABrAG4AbwB3AGwAZQBkAGcAZQAgAGEAbgBkACAAYwBvAGcAbgBpAHQAaQB2AGUAIABnAGEAcABzACAAZwBpAHYAZQAgAHQAaABlACAAcgBlAGEAcwBvAG4AIAB0AG8AIABiAGUAbABpAGUAdgBlACwAIAB0AGgAYQB0ACAAaQBuAGYAbwByAG0AYQB0AGkAbwBuACAAbQBhAG4AYQBnAGUAbQBlAG4AdAAgAGMAbwBuAGMAZQBwAHQAcwAgAGgAYQB2AGUAIABhACAAbQBvAHIAZQAgAHMAdQBiAHMAdABhAG4AdABpAGEAdABlAGQAIABjAG8AZwBuAGkAdABpAHYAZQAgAGIAYQBzAGkAcwAgAHQAaABhAG4AIAB0AGgAZQAgAGsAbgBvAHcAbABlAGQAZwBlACAAbQBhAG4AYQBnAGUAbQBlAG4AdAAgAG8AbgBlAHMALgAgAAUKAAAAAQAAAAAIAAAAAAVfAAAAAVUAAAABAQEEBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAFBh4AAABUAGkAbQBlAHMAIABOAGUAdwAgAFIAbwBtAGEAbgAZBgQAAABlAG4ACAAAAAAAMQIAAAEeAAAAAQYGAAAABAW9Qg8ACQYAAAAAGgYAAAAAGwYAAAAAAgkCAAAFdwAAAAFYAAAAAAEBAQEBBAYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4ABQYeAAAAVABpAG0AZQBzACAATgBlAHcAIABSAG8AbQBhAG4AGQYEAAAAZQBuAAgVAAAAABAAAABLAGUAeQB3AG8AcgBkAHMABWoBAAABVQAAAAEBAQQGHgAAAFQAaQBtAGUAcwAgAE4AZQB3ACAAUgBvAG0AYQBuAAUGHgAAAFQAaQBtAGUAcwAgAE4AZQB3ACAAUgBvAG0AYQBuABkGBAAAAGUAbgAICwEAAAAGAQAAOgAgAGsAbgBvAHcAbABlAGQAZwBlACAAbQBhAG4AYQBnAGUAbQBlAG4AdAAsACAAZQBuAHQAcgBlAHAAcgBlAG4AZQB1AHIAaQBhAGwAIABlAGMAbwBzAHkAcwB0AGUAbQAsACAAYwBvAG0AbQBvAGQAaQB0AHkALAAgAHUAbgBpAHYAZQByAHMAaQB0AHkALAAgAG8AcABlAHIAYQB0AGkAbwBuAGEAbAAgAGsAbgBvAHcAbABlAGQAZwBlACwAIABjAG8AZwBuAGkAdABpAHYAZQAgAGcAYQBwACwAIABpAG4AZgBvAHIAbQBhAHQAaQBvAG4ALAAgAGIAZQBsAGkAZQBmAAUKAAAAAQAAAAAIAAAAAAUKAAAACAUAAAANAAAAAAoAAAAAAAAAABEAAAAAuAEAAADcAAAAAAEAAQYSAAAAAgUAAAAAAwUAAAAABAUlFRMABQEDBgEABwEACAEACQYbAAAACgWghgEACwEBHAEADAUAAAAAHQEADQUAAAAADgYIAAAAAAEBAQP///8ZAQEbBn0AAAAAFAAAAAADAAAAAQUAAAAAAgXmRAAAAwEAARQAAAAAAwAAAAEFAAAAAAIF5kQAAAMBAAIUAAAAAAMAAAABBQAAAAACBeZEAAADAQADFAAAAAADAAAAAQUAAAAAAgXmRAAAAwEACxQAAAAAAwAAAAEFAAAAAAIF5kQAAAMBAAHNAAAAAAEAAQEAAgEAAwEABAYOAAAAQwBhAGwAaQBiAHIAaQAFBg4AAABDAGEAbABpAGIAcgBpAAcGDgAAAEMAYQBsAGkAYgByAGkABgYOAAAAQwBhAGwAaQBiAHIAaQATAQEIBBYAAAAKAQAMAQAOBQAAAAAPAQAQAQARAQASBQAAAAAUAQAVAQAWBBYAAAAXAQAYAQAZBgoAAAB1AGsALQBVAEEAGgYKAAAAYQByAC0AUwBBABsGCgAAAGUAbgAtAFUAUwAcBgIAAAAAAB4BAAIAAAAA">The article is devoted to the problem of the knowledge management in entrepreneurial ecosystems with the participation of universities, where knowledge exchanges should be intensive. It was important for our study to define, is the notion of a commodity could be used to knowledge. It is shown that the use of tacit and explicit knowledge as objects of management conceals the cognitive gaps between subjects’ consciousness and texts or other material presentations of information. Author proposed to supplement the subjective component of knowledge management with the notion of operative knowledge, which corresponds to the concept of knowledge as justified true belief. Operative knowledge may be defined as all of the words and phrases in consciousness, which appear when author seek an optimal version to transmit mental knowledge into explicit material form. By using the concept of operative knowledge, author is define the cognitive gap of actualization between tacit and operational knowledge, and also the cognitive gap of externalization between operational knowledge and the material form of information. It should be noted, that the concepts of operative knowledge and cognitive gaps give the reason to believe, that information management concepts have a more substantiated cognitive basis than the knowledge management ones. Keywords: knowledge management, entrepreneurial ecosystem, commodity, university, operational knowledge, cognitive gap, information, belief